The role of orthoses in the treatment of patellofemoral pain in runners - Bartold, S. (International SportMed Journal, 2001)
With the running boom of the mid-1970s came an increase in overuse injuries in runners. Foremost among these was patellofemoral pain. Because of this, much attention was focused on the biomechanics of the foot and lower leg and the influence that faulty foot biomechanics might have on anterior knee pain. Many researchers at this time felt that foot function was intimately linked to knee function and that patellofemoral pain was caused, at least in part, by abnormal foot function. Because of this, there was widespread acceptance that foot-orthotic devices could help treat anterior knee pain in general and patellofemoral pain specifically. Despite compelling anecdotal evidence that orthoses might be useful in treating patellofemoral pain, however, there has been little evidence to clarify the mechanism by which they can achieve a positive outcome. This article reviews the current literature and proposes a new theory for the mechanism of foot-orthotic action.